Glorifier le royaume et le souverain en temps de crise : émotions et royauté chez Christine de Pizan, les chroniqueurs de Charles VI, et Pierre de Ronsard - Morand Métivier, Charles-Louis (Studia Romanica Posnaniensia, 2018)
This article proposes to explore crises from seemingly different backgrounds and periods (the madness of Charles VI of France and the French Wars of Religion) to demonstrate how these elements were used by authors in order to create emotional narratives in support of the failing monarchy. In the two situations, the French community was constructed as an entity which duty was to support the king. However, the authors use different methods to transmit their messages. While Christine de Pizan and the chroniclers advocate for the building of an integrating, all encompassing community around the love of and for the king, Ronsard’s France is tasked at differentiating the Catholics and the Protestants, in an effort to construct France also as a monarchy loving community, of which the protestants are presented as the enemies.